International tax models towards multinational companies from the perspective of national welfare - Polezharova, L. V.; Goncharenko, M. A.; Gryechishkin, A. V. (Revista de la Universidad del Zulia, 2020)
The article is dedicated to the development of mathematical models to solve the real scientific task of supporting tax policies for counter-acting tax planning of multinational companies (MNCs) that are working in the field of production and engineering, forming the scheme international prosecutor, from the position of national welfare. Based on the analysis of the existing models of international taxes and on the peculiarities of the real mechanism of tax regulation of capital movement, new models have been developed with a balance orientation. The main points for this balance are: a) an approach aimed at determining the final results of international taxation from the perspective of national economies; b) Take as an example the gap between tax planning measures by multinationals and measures contrary to government tax planning. The approval of models with the case study of the multi-level structure in which, to counteract the tax planning of multinational companies, the Government uses rules of controlled transactions, demonstrated that due to the possibility of development of multinational companies in convenient and extraterritorial jurisdictions, for Government the final result of the application of these rules can be negative. Instead of additional income, you risk reducing the tax base and reducing budget income; And from the perspective of national welfare, this implies losing the income and capital of multinational companies. It is considered important that the rules for the taxation of multinational companies should not focus on taxes as such, but should encourage the maintenance of capital within the territory or facilitate the return of previously disinvested income.